Comprehensive analysis of the functional and immunological significance of ETV4 in pan-cancer and its validation in digestive tumors - Huang, Lingli; Li, Xujia; Huang, Silan; Jiang, Qi; Jiang, Chang; He, Wenzhuo; Cai, Yuchen; Guo, Guifang (Frontiers in Immunology, 2025)
BackgroundThe E26 transformation-specific (ETS) transcription factor family is widely expressed and implicated in tumorigenesis. Among them, ETV4 plays a crucial role in cancer progression. However, its broader impact on prognosis and immune regulation across different malignancies remains insufficiently understood.MethodsBased on public databases and our experimental validation, we systematically investigated the role of ETV4 in various cancers. Cytoscape, GSCALite, CancerSEA, STRING, HPA, TIGER, TISIDB, and R were used to assess ETV4’s expression and functional impact on basis of the TCGA and GTEx databases. Experimental validation included a range of methods such as CCK8 assays, clonogenic assays, migration assays, flow cytometry, RT-qPCR, immunohistochemistry (IHC), lentiviral transfection, and in vivo tumor formation assays.ResultsETV4 overexpression was detected in several cancer types and was associated with poor prognosis and specific molecular and immune subtypes. ETV4 was linked to overall survival in 10 of them. Furthermore, ETV4 played a key role in modulating multiple signaling pathways and was associated with immune regulation, particularly in melanoma and renal cell carcinoma, where its expression predicted immune responses. Knockdown of ETV4 in digestive tumors inhibited cell proliferation and migration, promoted apoptosis, and altered the expression of immune-related molecules. Further in vitro and in vivo analyses revealed that knockdown of ETV4 led to significant downregulation of FGL1 expression in BxPC3 cells and in tumors from Panc02 xenograft models. Kaplan-Meier Plotter analysis showed that lower FGL1 expression was associated with longer overall survival in patients receiving anti-PD1 therapy. In silico analysis using NCBI and UCSC genome databases further identified ETV4 as a putative transcription factor that may bind to the FGL1 promoter region, suggesting a potential regulatory relationship.ConclusionsETV4 shows differential expression across various cancer types and may serve as a potential prognostic biomarker in certain tumor types. Further validation in clinical samples and functional studies is warranted to clarify the biological role of ETV4 and its potential utility as a therapeutic target or prognostic indicator in pan-cancer.